'This is England, speak English!': a corpus-assisted critical study of language ideologies in the right-leaning British press. Issue 1 (1st January 2019) - Wright, David; Brookes, Gavin
ABSTRACT: This article examines right-leaning press representations of people living in the UK who can't speak English, or at least speak English well, following the 2011 Census, which was the first to ask respondents about their main language and proficiency in English. The analysis takes a corpus-assisted approach to critical discourse analysis, based on a 1.8 million-word corpus of right-leaning newspaper articles about 'speak(ing) English' in the years following this historic Census (2011 to 2016). The analysis reveals the tendency for the press to focus on immigrants – particularly in the contexts of education and health – who are represented with recourse to a series of argumentation strategies, or 'topoi'. Over the course of this paper, we argue that these topoi are problematic, as they present paradoxes, obscure the role of the Government in ensuring integration, overlook the difficulties of language learning and cultural assimilation, and generally contribute to a broader anti-immigrant UK media narrative which serves to legitimise exclusionary and discriminatory practices against people from minority linguistic and ethnic backgrounds.